HUBUNGAN JUMLAH BUNGA, JUMLAH DAUN, JUMLAH ANAK DAUN, JUMLAH CABANG, DAN TINGGI TANAMAN TERHADAP PERTUMBUHAN BIBIT TANAMAN KEMUNING (Murraya paniculata (L.) Jack) - Ray March Syahadat; Sandra Arifin Aziz (http://arl.faperta.ipb.ac.id/, 2013)
ABSTRACTThere is a problem that is frequently complained by the nursery which usually cultivated orange jessamine (Murraya paniculata (L.) Jack) from seed as a landscape plant. The problem is orange jessamine usually flowering although the size of the plants are still very small (about 5 cm) and even only has two leafs. These condition tends to be less favorable for the nursery because the orange jessamine grows slow because of vegetative growth was delayed due to the generative growth is underway. This study aims to see how important the presence of orange jessamine flowers in the nursery and how its relationship with branching, plant height, numberof leaves and number of leaflets. This research used a simple linear regression analysis and correlation of 150 orange jessamine plant seeds. The results showed only the correlation of the amount of flowers with plant height that has no significant correlation. Nevertheless, the presence of flowers in the nursery remains important because every increase in the number of flowers, there is also an increase in the number of branch, number of leaf, and number of leaflet.Keywords: Murraya paniculata (L.) Jack, rutaceae, flowers, landscape plants, plant nursery